PECULIARITIES OF CTENOCEPHALIDES GENUS FLEAS’ LOCALIZATION ON DOG BODY - Horb, K. O. (Scientific Progress & Innovations, 2020)
Parasitic disease caused by Ctenocephalides genus fleas is one of important problems in veterinary and human medicine. Ctenocephalosis is considerably spread among dogs and it also dangerous for human health. The invasion is accompanied by itching, restlessness, dermatitis, and anemia, growth and develop-ment retardation, especially of young animals. That is why timely and exact disease diagnosing is important, which will allow to conduct effectively the measures of prevention and fighting. The aim of the research was to study the peculiarities of ctenocephalosis causative agents’ localization on the infected dogs’ body. Ac-cording to the results of conducted parasitological examinations, it has been established that fleas of Ct. canis and Ct. felis species can be localized in any part of animal body. However, places of their localiza-tion on the dog body vary considerably. Parasitic insects of Ct. felis species were mostly found in the region of the median dorsal line of animals’ back (the average intensity of invasion made 4.06 specimens of imago fleas per dog) and in the inguinal region (the average intensity of invasion made 4.56 specimens per dog). At the same time, blood-sucking external parasites of Ct. canis species were mainly localized in the region of the tuber ishii (the average intensity of invasion made 2.55 specimens per dog). While comparing the indices of distributing fleas of various species on the dog body, reliable differences were established. The number of fleas of Ct. felis species was more in the region of the median dorsal line by 70.19 % (P<0,001), than the number of Ct. canis (1.24±0.45 specimens per head.). In the region of the tuber ishii on the dog body, the domination of Ct. canis (by 51.37 %, P<0.001) over Ct. felis (1.24±0.45 specimens per head.) was found. In the region of the left lateral animal body part, fleas of Ct. felis species prevailed (by 16.08 %, P<0.05) over Ct. canis (1.20±0.40 specimens per head). In the region of the right lateral body part, the number of fleas of various species did not differ reliably and varied from 1.35±0.63 specimens per head (in Ct. canis) to 1.45±0.68 specimens per head (in Ct. felis). In the inguinal region of the examined dogs’ body, fleas of Ct. felis species prevailed (by 74.34 %, P<0.001) over the fleas of Ct. canis species (1.17±0.38 specimens per head).